2022
DOI: 10.3389/fphar.2022.944147
|View full text |Cite
|
Sign up to set email alerts
|

Renovation as innovation: Repurposing human antibacterial peptide LL-37 for cancer therapy

Abstract: In many organisms, antimicrobial peptides (AMPs) display wide activities in innate host defense against microbial pathogens. Mammalian AMPs include the cathelicidin and defensin families. LL37 is the only one member of the cathelicidin family of host defense peptides expressed in humans. Since its discovery, it has become clear that they have pleiotropic effects. In addition to its antibacterial properties, many studies have shown that LL37 is also involved in a wide variety of biological activities, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 156 publications
(209 reference statements)
0
7
0
Order By: Relevance
“…Regarding the secondary structures, AMPs are classified as linear α‐helical peptides, β‐sheet peptides, peptides with extended structure, and peptides with both α‐helix and β‐sheet conformation or with more complex topologies 30 . Based on their biological activity, we can distinguish between AMPs with antibacterial, 31 antifungal, 32 antiviral, 33 antiparasitic, 34 and anticancer properties 35 . Based on their primary mechanism of action, AMPs can be divided in two major groups: non‐membrane targeting and membrane targeting AMPs, even if recent evidence showed that some AMPs not only act on the membrane but they can also activate a cascade of reactions within bacterial cells 36,37 .…”
Section: The Need For New Antiviral Compounds and The Potential Of Ampsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the secondary structures, AMPs are classified as linear α‐helical peptides, β‐sheet peptides, peptides with extended structure, and peptides with both α‐helix and β‐sheet conformation or with more complex topologies 30 . Based on their biological activity, we can distinguish between AMPs with antibacterial, 31 antifungal, 32 antiviral, 33 antiparasitic, 34 and anticancer properties 35 . Based on their primary mechanism of action, AMPs can be divided in two major groups: non‐membrane targeting and membrane targeting AMPs, even if recent evidence showed that some AMPs not only act on the membrane but they can also activate a cascade of reactions within bacterial cells 36,37 .…”
Section: The Need For New Antiviral Compounds and The Potential Of Ampsmentioning
confidence: 99%
“…30 Based on their biological activity, we can distinguish between AMPs with antibacterial, 31 antifungal, 32 antiviral, 33 antiparasitic, 34 and anticancer properties. 35 Based on their primary mechanism of action, AMPs can be divided in two major groups: non-membrane targeting and membrane targeting AMPs, even if recent evidence showed that some AMPs not only act on the membrane but they can also activate a cascade of reactions within bacterial cells. 36,37 To the first group belong the peptides that enter the cell and interact with specific targets by inhibiting intracellular processes such as protein biosynthesis, 38 nucleic acid biosynthesis, 39 protease activity and cell division.…”
Section: The Need For New Antiviral Compounds and The Potential Of Ampsmentioning
confidence: 99%
“…Biomedical Application Peptide Surgical site infection (SSI) LL-37 [15], hBD2&3 [16], Protegrins [17], Histatins [18], Ranalexin [19], Pexiganan [20], Magainin [21], HNP1 [22] Contact lens-associated microbial keratitis (CLMK) α-MSH [23], Melimine [24], Pexiganan [25], Bacitracin [26], Dermcidin [27] Dental applications LL-37 [28], Dermaceptin [29], Nisin, Histatins [30], hBD1 [31], human beta-defensin-3 [32], human beta-defensin-5, Cateslytin [33], Myxinidin [34], HHC-36 [34] Bone-graft applications KLD [35], E14LKK [36] Tissue generation DermaceptinS4 [37], Thanatin [38], LLKKK18 [39], DPK-060 [40], SMAP-29 [41], G3KL [42], G3R, MSI-78 Anticancer agents pAntp [43], KT2 [44], RT2 [45], LL37 [46], LTX-315, [46] melittin [47]…”
Section: Sl Nomentioning
confidence: 99%
“…Although the exact mechanism of wound repair is still elusive, there is a supposed effect of LL-37 in modulating the inflammatory response and driving angiogenesis together with re-epithelialization [ 125 , 141 ]. Such a wide array of modulatory cell activities also led to the repurposing of LL-37 for cancer treatment [ 142 ]. Moreover, its role in oral homeostasis is also known, and it is not related merely to microbiota stabilization [ 143 ].…”
Section: Clinical Application Of Ampsmentioning
confidence: 99%